Differences in Health-Related Quality of Life in Older People with and without Sarcopenia Covered by Long-Term Care Insurance - Masahiro Kitamura; Kazuhiro P. Izawa; Kodai Ishihara; Peter H. Brubaker; Hiroaki Matsuda; Soichiro Okamura; Koji Fujioka (MDPI AG, 2022)
Background: As a result of the increase in older people covered by long-term care insurance (LTCI), prevention of sarcopenia and maintenance and improvement of health-related quality of life (HRQOL) have become important themes. This study aimed to clarify both the differences in HRQOL in older people with and without sarcopenia covered by LTCI and the correlation between HRQOL and physical function. Methods: Participants were 101 older people with LTCI at a daycare center in Japan. We investigated clinical factors using the EuroQol five-dimension three-level questionnaire (EQ-5D-3L). Analysis was by unpaired t-test, Mann-Whitney U test, chi-square test, analysis of covariance, Pearson's correlation coefficient, and Spearman's rank correlation coefficient. Results: Compared to the no sarcopenia group (n = 40), the sarcopenia group (n = 24) had significantly lower body mass index, skeletal muscle mass index, gait speed, EQ-5D-3L, and adjusted EQ-5D-3L (p < 0.05). The EQ-5D-3L showed a significant correlation with handgrip strength in the sarcopenia group (p = 0.02) and significant correlations with gait speed and one-leg standing time (both, p = 0.01) in the no sarcopenia group. Conclusion: We clarified differences in HRQOL in older people with and without sarcopenia covered by LTCI. This information on the interrelationship between HRQOL and physical function may help maintain and improve HRQOL in these people.